Quality improvement report: setting up a hospital at night service, limitations of bleep filtering and using an electronic task management system. Issue 1 (30th March 2021) - Saqib, Aaisha; Cairney, Kevin; Mcintyre, Karen; Coutts, Emma; Stephens, Tamara; Roberts, Lesley; Banerjee, Sandip
Abstract : The 'hospital at night' concept was developed at a joint conference of the London Deanery and Clinical Staff in 2002, as an issue for education and service provision. At the start of the project, our trust had issues with both the structure of the hospital at night handover and the working practices overnight. The vision was to improve team working out of hours, expedite review of sick patients and reorganise care to seek a reduction in bleeps to medical junior doctors overnight in a way that all patients had access to the right person with the right skills for their needs at the right time. The hospital at night project at our hospital was started in 2019 by a multidisciplinary working group. We tried bleep filtering for 4 months and this was later followed on by the development of an electronic out of hour's task list as part of our hospital at night set-up. The bleep analysis data showed an improved distribution of workload but the process was dependent on individuals. The electronic task management system was built in pre-existing online software. The system helped prioritise and review tasks requested by nurses on medical wards. But it was not without its limitations. We worked with the local information technology (IT) team to improve speed and proposed developing an IT solution that is fast and not desktop based to ensure tasks can be assigned and viewed while on the go. The project was overall a success as it demonstrated positive feedback from junior doctors, improved perception of teamwork and ability to take rest breaks. It also demonstrated a drop in ward-based cardiac arrest rates. The hospital at night project at our trust remains a work in progress, but a lot of positive changes have been delivered.